2009
DOI: 10.1056/nejmoa075760
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitors of Factor VIII in Black Patients with Hemophilia

Abstract: Background Black patients with hemophilia A (factor VIII deficiency) are twice as likely as white patients to produce inhibitors against factor VIII proteins given as replacement therapy. There are six wild-type factor VIII proteins, designated H1 through H6, but only two (H1 and H2) match the recombinant factor VIII products used clinically. H1 and H2 are found in all racial groups and are the only factor VIII proteins found in the white population to date. H3, H4, and H5 have been found only in blacks. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
206
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(217 citation statements)
references
References 48 publications
5
206
1
5
Order By: Relevance
“…It is known that patients carrying mutations precluding FVIII synthesis, defined as null mutations (i.e., large deletions, inversions and nonsense mutations), are more susceptible to developing inhibitors (Schwaab et al, 1995;Goodeve & Peake, 2003). More recently, it has been reported that specific F8 polymorphisms may play a role in the increased inhibitor risk observed in black patients (Viel et al, 2009). In addition, human leucocyte antigen (HLA) class II molecules and polymorphisms of immune-regulatory genes (IL10, TNF and CTLA4) have been shown to influence the risk of inhibitor formation (Astermark et al, 2006a(Astermark et al, ,b, 2007Pavlova et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that patients carrying mutations precluding FVIII synthesis, defined as null mutations (i.e., large deletions, inversions and nonsense mutations), are more susceptible to developing inhibitors (Schwaab et al, 1995;Goodeve & Peake, 2003). More recently, it has been reported that specific F8 polymorphisms may play a role in the increased inhibitor risk observed in black patients (Viel et al, 2009). In addition, human leucocyte antigen (HLA) class II molecules and polymorphisms of immune-regulatory genes (IL10, TNF and CTLA4) have been shown to influence the risk of inhibitor formation (Astermark et al, 2006a(Astermark et al, ,b, 2007Pavlova et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Disparities are reported among adolescents 14 and among children with special healthcare needs (CSHCN). [15][16][17][18] Reports on the impact of race and ethnicity in hemophilia have been limited to the higher prevalence of African Americans who develop inhibitors, 19,20 septic arthritis, 21 and joint ROM limitations. 7 There are no comprehensive reports on the impact of race and ethnicity on the pediatric U.S. hemophilia population.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the significantly higher inhibitor occurrence in the AfricanAmerican population, and is currently being investigated in detail. 18 …”
Section: Prophylaxismentioning
confidence: 99%